Modelling one-dimensional reactive transport of toxic contaminants in natural rivers. (March 2021) - Kim, Byunguk; Seo, Il Won; Kwon, Siyoon; Jung, Sung Hyun; Choi, Yongju
Abstract: Solute transport models are widely employed to the predict spatio-temporal fate of contaminants in rivers. However, most previous studies have assumed that contaminants spilled are unreactive; they disregard the inherent reactivity of contaminants in water. The Reactive Solute Transport Model (RSTM) (Gooseff et al., 2005) includes lumped decay terms to reflect the decayability of the chemicals, but its applicability was still poor due to dependence on an optimization method. The purpose of this study is to perform reactive transport modelling considering chemicals' reactivities for sorption, volatilization, and biodegradation. To this end, we manipulated the governing equations of the RSTM and suggested theoretical and empirical methods of estimating the key parameters of the reaction terms. The results showed, for example, that benzene lost 57.7% of its primary mass after being transported 4.54 km downstream due to its high volatility. Also, the arrival time of toluene was delayed by 10.4% due to adsorption. Highlights: Simulation of reactive solute transport with toxic chemicals. Derivation of analytical solution of a reactive solute transport model. Tracer tests in second-order natural river. Estimation of decay parameters without optimization techniques.